2022
DOI: 10.1007/s10552-021-01546-7
|View full text |Cite
|
Sign up to set email alerts
|

Geographic determinants of colorectal cancer in Louisiana

Abstract: Purpose Currently, rural residents in the United States (US) experience a greater cancer burden for tobacco-related cancers and cancers that can be prevented by screening. We aim to characterize geographic determinants of colorectal cancer (CRC) incidence in Louisiana due to rural residence and other known geographic risk factors, area socioeconomic status (SES), and cultural region (Acadian or French-speaking). Methods Primary colorectal cancer diagnosed … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
1

Year Published

2022
2022
2022
2022

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 30 publications
0
1
1
Order By: Relevance
“…Contrary to our ndings, studies in the United States have shown that the risk of colorectal cancer is associated with low socio-economic status (SES) at both the individual and regional levels [36][37][38]. Danos et al [39] also, unlike us, found a signi cant increase in CRC risk among residents of areas with low SES. It is identi ed that factors such as socio-economic status have been the cause of social inequalities in various cancer outcomes [15].…”
Section: Discussioncontrasting
confidence: 99%
“…Contrary to our ndings, studies in the United States have shown that the risk of colorectal cancer is associated with low socio-economic status (SES) at both the individual and regional levels [36][37][38]. Danos et al [39] also, unlike us, found a signi cant increase in CRC risk among residents of areas with low SES. It is identi ed that factors such as socio-economic status have been the cause of social inequalities in various cancer outcomes [15].…”
Section: Discussioncontrasting
confidence: 99%
“…6 Experts remain puzzled as to the cause of the alarming rise in EOCRC, but some potential factors include the Western-style diet, obesity, physical inactivity, socioeconomic status, and antibiotic use, especially during the early prenatal to adolescent period. 7,8 A family history of CRC and a genetic predisposition for the disease are known risk factors. 9 A Utah-focused study by Ochs-Balcom et al 10 found that, for patients of any age, having a first-, second-, or third-degree relative with EOCRC conferred a 2.64-fold, 1.96-fold, and 1.3-fold higher risk for developing CRC, respectively.…”
mentioning
confidence: 99%